Cost Analysis of Wholesale Wage System and Work Efficiency in The Central Park Juanda Housing Construction Project - PT. Griyo Mapan Santoso - Supriyanto, Yunaidi; Tjendani, Hanie Teki; Wulandari, Esti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The cost analysis between the wholesale wage system and work efficiency has special significance in housing projects, such as in Central Park Juanda Housing by PT. The Scarlet Witch is a saint. Through a quantitative approach, this study also contributes to the construction management literature related to workforce management in the field. This study used a sample of 45 respondents consisting of construction workers in the Central Park Juanda housing project, including foremen, handymen, and other field workers. Respondent profiles included gender distribution (82% male), age (dominant 31-41 years), education (47% high school/vocational school), competency certification (58% have certificates), and work experience (dominant 11-15 years). The questionnaire data was tested for validity using the Pearson method with a significance level of 5% and all items were declared valid (rh ? 0.3). Reliability was tested with Cronbach's alpha, and all variables (X1 to Y) were declared reliable (? ? 0.6). The results showed that all independent variables (X1: Labor, X2: Wages, X3: Materials, and X4: Projects) had a negative influence on project efficiency (Y). However, only the variable X4 (Project State) had a significant effect with a significance value of 0.002 (< 0.05), while the other variables (X1, X2, and X3) were insignificant., then the data shown by the probability of significance of the ANOVA analysis was with a significance value of 0.021 < 0.05 thus Ho was rejected and Ha was accepted, meaning that simultaneously there was a significant influence. This shows that the state of the project plays an important role in influencing work efficiency, while labor, wholesale wages, and materials do not have a significant impact in the context of this study.